Multifunctional agriculture: relevance for tourism in Mexico - Velázquez Castro, Judith Alejandra (Revista Mexicana de Ciencias Agrícolas, 2018)
The development of tourism activity is closely related to the attractiveness of tourist destinations. That is why, when analyzing the link between agriculture and tourism, it is possible to identify the potential that it has to offer in the tourist market. Thus, the objective of this paper was to analyze the multifunctional nature of agriculture and its potential for tourism in Mexico; in order to promote economic, environmental and social benefits for the interested parties (companies, community, government, tourists). Referring to examples of practices and strategies to promote stronger links between the agricultural and tourism sectors. Given the multifunctional nature of agriculture, the findings of this research indicate that there is a solid basis for the development of agrotourism or agricultural tourism in Mexico; with specific and potential actions, mainly related to promotional strategies for tourist products in different regions of the country. The above, based on the principles of sustainable development: protection of the natural environment, long-term gains and quality of life for farmers and their communities. Finally, this research raises the urgency of designing public policies that encourage agrotourism and promote regional development based on priorities and activities defined according to each territorial context.